PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE THE POWER OF TWO UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS IV SD NEGERI 37 PEKANBARU - Ningsih, Rosliyah Deswina; Marhadi, Hendri; ', Syahrilfuddin (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The problem in this research is the low student learning outcomes IPS. This is reflected in the value of students who achieve KKM (Minimum Criteria for completeness) only 11 (36.67%) of 30 students. While KKM applied at the school is 75, meaning many students who have not reached the KKM is 19 people (63.33%). The purpose of this research is to improve learning outcomes IPS IVE grade students of SD Negeri 37 Pekanbaru with the implementation of cooperative learning model type The Power of Two. Cooperative learning model type The Power of Two is part of a cooperative learning model in which there is a discussion that is more about cooperation by the two students by way of exchanging ideas and comparing with the results of the discussion another couple. After that, it can be asserted in an effort to solve a problem with exercise courage and shaping students to think critically about a problem that exists. Analysis of the research data base score of social science learning outcomes of students increased in the first cycle and the second cycle. This increase is evident from the results of student learning before using cooperative learning model type The Power of Two with averages of students is 58.83, increasing to 69.33 in the first cycle and increased again to 81.67 in the second cycle. It can be concluded that the implementation of cooperative learning model type The Power of Two can improve learning outcomes IPS fourth grade students of SD Negeri 37 Pekanbaru.Key Words: The Power Of Two, Learning Outcomes